Nanocatalysts‐Augmented and Photothermal‐Enhanced Tumor‐Specific Sequential Nanocatalytic Therapy in Both NIR‐I and NIR‐II Biowindows. Issue 5 (9th December 2018) - Feng, Wei; Han, Xiuguo; Wang, Rongyan; Gao, Xiang; Hu, Ping; Yue, Wenwen; Chen, Yu; Shi, Jianlin
Abstract: The tumor microenvironment (TME) has been increasingly recognized as a crucial contributor to tumorigenesis. Based on the unique TME for achieving tumor‐specific therapy, here a novel concept of photothermal‐enhanced sequential nanocatalytic therapy in both NIR‐I and NIR‐II biowindows is proposed, which innovatively changes the condition of nanocatalytic Fenton reaction for production of highly efficient hydroxyl radicals (OH) and consequently suppressing the tumor growth. Evidence suggests that glucose plays a vital role in powering cancer progression. Encouraged by the oxidation of glucose to gluconic acid and H2 O2 by glucose oxidase (GOD), an Fe3 O4 /GOD‐functionalized polypyrrole (PPy)‐based composite nanocatalyst is constructed to achieve diagnostic imaging‐guided, photothermal‐enhanced, and TME‐specific sequential nanocatalytic tumor therapy. The consumption of intratumoral glucose by GOD leads to the in situ elevation of the H2 O2 level, and the integrated Fe3 O4 component then catalyzes H2 O2 into highly toxic OH to efficiently induce cancer‐cell death. Importantly, the high photothermal‐conversion efficiency (66.4% in NIR‐II biowindow) of the PPy component elevates the local tumor temperature in both NIR‐I and NIR‐II biowindows to substaintially accelerate and improve the nanocatalytic disproportionation degree of H2 O2 for enhancing the nanocatalytic‐therapeutic efficacy, which successfully achieves a remarkable synergistic anticancer outcome with minimal side effects. Abstract : Based on the unique tumor microenvironment for achieving tumor‐specific therapy, a novel concept of photothermal‐enhanced sequential nanocatalytic therapy in both NIR‐I and NIR‐II biowindows is proposed, which innovatively changes the condition of the nanocatalytic Fenton reaction for highly efficient production of hydroxyl radicals and consequently suppressing the tumor growth.